Hypolipidemic Activity on Ethanolic Extract of Leaves of Ziziphus oenoplia - Lalitha Eswari, M (International Journal of Pharmaceutical & Biological Archive, 2013)
Hypolipidemic Activity on Ethanolic Extract of Leaves of Ziziphus oenoplia